The Relationship of Self-Efficacy with Diet Compliance in Type 2 Diabetes Mellitus Patients in Puskesmas Gumawang, OKU Timur Regency - Ahsan; Nurul Rahmawati; Annisa Wuri Kartika (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
Dietary compliance in diabetes patients is vital to developing good outcomes for better health. One of the biggest problems in managing diet for patients is feeling bored and pressured with the menu that has been provided. The impact is that they show unwillingness and inability to follow a diet program. Adherence to this diet emphasizes the role and self-efficacy that requires awareness and intention from people who manage diabetes mellitus. This study aimed to determine the relationship between self-efficacy and dietary compliance in patients with Diabetes Mellitus type 2 at the Gumawang Primary Health Center, East OKU district. This study used a cross-sectional approach with 53 respondents. The sampling technique used is purposive sampling. Data collection using research instruments in two questionnaires, namely the Diabetes Management Self Efficacy Scale (DMSES) and Dietary Compliance by Haryono modified by Permatasari (2014). The results of the univariate analysis showed that self-efficacy was in the reasonably good category and diet compliance was in the good category. Based on bivariate analysis, it is known that the p-value is 0.000 <0.005 with a correlation coefficient of 0.773, which means that there is a solid significant correlation between the self-efficacy variable and dietary compliance. It is recommended to create a program to improve patient self-efficacy, one of which is to create a Self-Help Group program for patients with Diabetes Mellitus.